2017
DOI: 10.1080/02607476.2017.1342051
|View full text |Cite
|
Sign up to set email alerts
|

Learning inter-professional teamwork during university studies: a case study of student-teachers’ and social work students’ shared professional experiences

Abstract: This is a self-archived version of an original article. This version usually differs somewhat from the publisher's final version, if the self-archived version is the accepted author manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Considering the emerged role of collaboration, training student teachers to work within teams (when taking decisions, solving problems, planning educational task), as well as to be aware and foster their interpersonal skills, could be useful to prepare them to face the school context. Studies addressing these dimensions have shown that when preservice teachers take part to preparation programs fostering these dimensions are better at dealing with interpersonal conflicts, empathetically relate to children, families, and colleagues, and better collaborate with other professionals [101,102].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the emerged role of collaboration, training student teachers to work within teams (when taking decisions, solving problems, planning educational task), as well as to be aware and foster their interpersonal skills, could be useful to prepare them to face the school context. Studies addressing these dimensions have shown that when preservice teachers take part to preparation programs fostering these dimensions are better at dealing with interpersonal conflicts, empathetically relate to children, families, and colleagues, and better collaborate with other professionals [101,102].…”
Section: Discussionmentioning
confidence: 99%
“…However, both in the field of teacher education and in other fields, the need for multidisciplinary studies and closer collaboration with students from several fields has been identified. Collaborative actions practiced during master's studies might promote a collaborative culture and mutual respect between different professional groups (see Lakkala et al, 2017;also Lakkala et al, 2021). In addition, professionals in various fields have found the development of transparent interprofessional practices as being necessary to ensuring the functioning of interprofessional collaboration (Leppäkoski et al, 2017).…”
Section: Interprofessional Collaboration As An Integral Part Of Stude...mentioning
confidence: 99%
“…For example, in all of our school cases there were several professionals working with the students, their families, and teachers during the school day. When the collaborative network expands beyond the teaching staff, there are even more possibilities for misunderstandings between parties who represent different professional backgrounds [24]. In interprofessional teamwork, the role of an individual as a part of the group [8] and the social and professional relationships in the team [23] are important.…”
Section: Theoretical Background 21 the Collaborative Professional Omentioning
confidence: 99%
“…It contains the idea of looking at something together from the perspectives of one's own and another's profession, learning from professionals in other fields [8]. The difficulty of interprofessional teamwork lies in the dilemmas that may arise from the different professional orientations and each team member's abilities to detect his/her own role as a promoter of collaboration and negotiator of new goals in boundary spaces [8,24]. The premise of interprofessional teamwork is shared expertise, whereby team members create goals and strategies together, instead of offering ready-made solutions based on one's own profession [23].…”
Section: Introductionmentioning
confidence: 99%